2022
DOI: 10.3389/fnut.2022.871062
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Network Analysis for Front-of-Pack Labeling in China

Abstract: BackgroundFront-of-pack (FoP) labeling on packaged foods is recommended by the World Health Organization (WHO) to reduce diet-related non-communicable diseases, but it has not yet been implemented in China. The introduction of FoP labeling is driven by multiple institutions and stakeholders. This study aimed to identify key institutional actors involved in FoP labeling and describe links between actors to support future FoP labeling policies and programmes in China.MethodsThe Net-Map method was adopted. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The Chilean FOPWL and the Chinese Healthier Choice Logo were used to cross-compare the nutrient content of processed meat products in China, the UK, and France. China Consumer Surveys on FOPL [ 30 , 31 , 32 ] and other studies on the view of stakeholders on the FOPL policy in the Chinese context [ 33 , 34 ] indicated that Chinese residents and stakeholders tended to prefer interpretive FOPL. Furthermore, due to the limitations of mandated labeling contents of Chinese food labeling standards, summary-based graded NP models that evaluate overall nutritional quality of foods, such as Nutri-Score, cannot be used in this study to evaluate the nutrient content of products.…”
Section: Methodsmentioning
confidence: 99%
“…The Chilean FOPWL and the Chinese Healthier Choice Logo were used to cross-compare the nutrient content of processed meat products in China, the UK, and France. China Consumer Surveys on FOPL [ 30 , 31 , 32 ] and other studies on the view of stakeholders on the FOPL policy in the Chinese context [ 33 , 34 ] indicated that Chinese residents and stakeholders tended to prefer interpretive FOPL. Furthermore, due to the limitations of mandated labeling contents of Chinese food labeling standards, summary-based graded NP models that evaluate overall nutritional quality of foods, such as Nutri-Score, cannot be used in this study to evaluate the nutrient content of products.…”
Section: Methodsmentioning
confidence: 99%
“…Consumers of commonly consumed foods are particularly concerned. To this end, the states have developed and introduced a series of food standards to ensure consumer safety [4][5][6]. By 2020, a food safety supervision system based on risk analysis and supply chain management has been established, and major regional and systemic food safety risks have been controlled.…”
Section: Introductionmentioning
confidence: 99%